The Virtue of Patience - Grills, Scott (Qualitative Sociology Review, 2020)
Shaffir (1998:63) writes, “We must learn to reclaim the virtue of patience. When we enhance the pace of doing research, it is often at the expense of acquiring a deep appreciation of the research problem.” This paper engages Shaffir’s claim by examining the importance of undertaking a patient sociology. What is the virtue to be found in prolonged and sustained work? How does this speak to the relationships found in field research and in the identities that inform our work as researchers and theorists? In contrast to recent trends towards various versions of instant or short-term ethnography (e.g., Pink and Morgan 2013) this paper argues for the merits of “slow” ethnography by examining the advantages of relational patience, perspectival patience, and the patience required to fully appreciate omissions, rarities, and secrets of the group.